Variasi Biaya Sectio Caesaria di Rumah Sakit Indonesia - Tetriadi, Tetriadi; Nurwahyuni, Atik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
Pricing / variation of costs is one of the strategic steps that must be taken because it refers to costs incurred, both marginal and total costs, including indirect costs (overhead costs). Cesarean section (SC) surgery is one of the most common actions performed in the operating room which also requires careful planning of service costs, so that the appropriate price setting for the hospital can do activities without reducing service quality. This paper aims to look at the different costs of SC in Indonesia based on the class / level of the hospital and hospital ownership, whether the hospital is owned by the government or private / private as well as classes or treatment rooms. Another purpose of this paper is to look at the different proportions of costs that occur in the SC cost component. The method used in this paper is a comparison of data or literature studies from 20 hospitals in the UI library, and to be able to compare these data and avoid the difference in inflation, it is necessary to do the data collection or presentation of valuation (PV). The case of SC chosen was a normal case of SC without emergency and complication. There are intervals / variations that are quite wide service costs and the proportion of cost components (services, accommodation, medical and drug examinations, stationery and BHP) in both public and private hospitals in various types of hospitals. The role of hospital management in determining service rates / prices is one of the keys to success in hospital marketing strategies, reinforced from research from many other countries. Hospitals whose proportion of service cost components are not in accordance with existing regulations so that they immediately revise so that there is no disruption in hospital services, especially since the UHC was declared by the government. Marketing, Sectio Caesaria, Hospital Class Variation, Cost Proportion.